The Metaconversation: The Recursive Property of Language as a Key to Organizing - Robichaud, Daniel; Giroux, Hélène; Taylor, James R. (Academy of Management Review, 2004)
Daniel Robichaud, Hélène Giroux, James R. Taylor, The Metaconversation: The Recursive Property of Language as a Key to Organizing, The Academy of Management Review, Vol. 29, No. 4 (Oct., 2004), pp. 617-634